Dukungan dan Koping Keluarga dalam Motivasi Pengobatan Penderita Diabetes Melitus - Alva Cherry Mustamu; Sjarfan Sjarfan; Nur Hafni Hasim (Poltekkes Kemenkes Yogyakarta, 2020)
There are about 10 million people with diabetes mellitus in 2015 and Indonesia ranks seventh as the country with the most diabetes mellitus population in the world. Diabetes mellitus is a disease that causes damage to pancreatic ? cells that produce insulin. Motivation from the family is one way that patients can undergo treatment for diabetes mellitus regularly, so family support and coping are needed to overcome the problem. This study aims to determine the relationship between support and family coping with the motivation to treat diabetes mellitus in Sorong District Hospital. This research is a descriptive analytic study with cross-sectional design on 41 respondents. Data collection using questionnaire sheets. The results of calculating the relationship between family coping and treatment motivation using the Spearman rank correlation showed r = 0.679 and ?-value = 0,000. The results of the calculation of the relationship between family support and treatment motivation using the chi square test ?-value = 0,000. this study found that there is a coping and family support and treatment motivation. Factors that can increase motivation include family support and coping. Further research can examine the relationship between the level of knowledge and treatment motivation for clients of diabetes mellitus.g the chi square test ?-value = 0,000. this study found that there is a coping and family support and treatment motivation. Factors that can increase motivation include family support and coping. Further research can examine the relationship between the level of knowledge and treatment motivation for clients of diabetes mellitus.